(untitled) (Journal of the College of Basic Education, 2022)
The presence of Islamic banks in the financial and banking system in the world represents a somewhat new experience. The purpose of establishing Islamic banks is that banking work in society is in conformity with Islamic jurisprudence in its general form. To manage the economic business and therefore the individual must be subject to the directives of the original owner, hence the following question (Is the economic work in Islam within the controls of Sharia or not?).